2017
DOI: 10.1177/1010428317698354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irinotecan on HMGB1, MMP9 expression, cell cycle, and cell growth in breast cancer (MCF-7) cells

Abstract: Irinotecan is a natural alkaloid agent widely used in cancer therapy. High-mobility group protein B1 as a non-histone chromosomal protein plays a fundamental role in gene expression and inflammation. In this study, the effect of irinotecan on high-mobility group protein B1 and MMP9 content, gene expression, cell cycle, and cell growth in human breast cancer cells (MCF-7) was investigated. The cells were exposed to various concentrations of irinotecan and the viability determined by trypan blue exclusion and 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Therefore our present results are consistent with these previous reports. Although CPT induced G2/M phase arrest in our study, S phase arrest in MCF-7 cells [48] and S phase and G2/M arrest in Caco-2 cells and CW cells have been reported [49]. In our study, GF induced M/G1 arrest, whereas G2/M phase arrest was reported in HL-60 cells [50].…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore our present results are consistent with these previous reports. Although CPT induced G2/M phase arrest in our study, S phase arrest in MCF-7 cells [48] and S phase and G2/M arrest in Caco-2 cells and CW cells have been reported [49]. In our study, GF induced M/G1 arrest, whereas G2/M phase arrest was reported in HL-60 cells [50].…”
Section: Discussioncontrasting
confidence: 48%
“…Flow cytometry detects apoptosis via analyzing the difference of fluorescence intensity among normal cells, apoptotic cells and dead cells, it reflects apoptosis at a cellular level, while the expression of apoptosisassociated proteins detected by western blot assay reflects apoptosis at a molecular level (45,49). Secondly, 7-ethyl-10-hydroxy-camptothecin (SN-38), the metabolic product of CPT-11, induces DNA damage, and is the primary mechanism for the pharmacological effect of CPT-11 (50). Studies have reported that CPT-11 induces apoptosis of colon cancer cells through the p53 signaling pathway, and CPT-11 alone or in combination with other drugs may induce apoptosis via altering the expression of Bcl-2 family, caspase family and survival-associated genes in cancer cells (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of cell cycle arrest to prevent the cell proliferation is one of the effective ways used by cytotoxic drugs. These drugs play an anticancer role via arresting G0/G1, S or G2/M phases, thereby inhibiting cell growth, and eventually leading to apoptosis 55 , 56 . Following treatment of MDA-MB231 with various concentrations of OEO/thymol, results clearly verified that OEO/thymol has the potential to arrest MDA-MB231 cell lines at S-phase significantly.…”
Section: Discussionmentioning
confidence: 99%